Evaluation of a conceptual model for digital interfaces for garment composition labels: an integrated approach to Information Design and Inclusive Design - Oliveira, Rodrigo Diego de; Smythe, Kelli Cristine Assis Silva; Okimoto, Maria Lucia Leite Ribeiro (InfoDesign, 2025)
This article researches the effectiveness of a conceptual model for digital clothing composition labels, designed for both domestic and professional users, by integrating principles of information design and inclusive design. Through an interaction analysis and the application of a satisfaction questionnaire with eight participants, the authors conducted a quantitative and qualitative evaluation to assess improvements in the understanding of information related to composition, washing care, symbols, and additional guidance, such as risk alerts, dimensions, and descriptions of the garment’s visual characteristics, among other aspects. The results indicate that digital interfaces can overcome the limitations of physical labels identified in previous studies, particularly regarding difficulties in reading, understanding, and accessibility for individuals with blindness, low vision, color blindness, and deafness, offering a more satisfying and accessible experience for diverse user profiles.